The influence of social support, perception, and maternal behavior in preventing stunting cases in Indonesia - Mindarsih, Eko; Akhyar, Muhammad; Wiboworini, Budiyanti; Suminah, Suminah (Intelektual Pustaka Media Utama, 2024)
The research aims to analyze the simultaneous influence of social support, perception and maternal behaviour in preventing stunting cases in Indonesia. The research adopts the quantitative cross-sectional approach to provide an explanatory survey. The sample was taken based on proportional random sampling. A sample size of 220 pregnant women in the second and third trimesters participated in this study. The research instrument employed was a questionnaire, which underwent validation by 12 experts using Aiken's V content validity index. The collected data were analyzed utilizing the Lisrel program, employing multiple linear regression tests and structural equation modeling (SEM) analysis. The findings of this study revealed that the perception, social support, and behavior of pregnant women were reasonably categorized. Social support has a significant positive influence on perception. Social support and perception simultaneously have a significant positive influence on the behaviour of pregnant women. In conclusion, the behavior of pregnant women can be recommended as the solution in the primary prevention of stunting.